A Statistical and Demographic Profile of the US Temporary Protected Status Populations from El Salvador, Honduras, and Haiti. (September 2017) - Warren, Robert; Kerwin, Donald
Executive Summary 1 This report presents detailed statistical information on the US Temporary Protected Status (TPS) populations from El Salvador, Honduras, and Haiti. TPS can be granted to noncitizens from designated nations who are unable to return to their countries because of armed conflict, environmental disaster, or other extraordinary and temporary conditions. In January 2017, an estimated 325, 000 migrants from 13 TPS-designated countries resided in the United States. This statistical portrait of TPS beneficiaries from El Salvador, Honduras, and Haiti reveals hardworking populations with strong family and other ties to the United States. In addition, high percentages have lived in the United States for 20 years or more, arrived as children, and have US citizen children. The paper finds that: The labor force participation rate of the TPS population from the three nations ranges from 81 to 88 percent, which is well above the rate for the total US population (63 percent) and the foreign-born population (66 percent). The five leading industries in which TPS beneficiaries from these countries work are: construction (51, 700), restaurants and other food services (32, 400), landscaping services (15, 800), child day care services (10, 000), and grocery stores (9, 200). TPS recipients from these countries live in 206, 000 households: 61, 000 of these households (about 30 percent) have mortgages. About 68, 000, or 22 percent, of the TPS population from these nations arrived as children under the age of 16.